A prospective double blind study comparing the effects of oxytocin and human chorionic gonadotrophin as trigger for ovulation. (January 2014) - Mehrotra, S.; Singh, U.; Gupta, H. P.; Tandon, I.; Saxena, P.
<x xml:space="preserve">Abstract</x> This study was undertaken to compare the effect of oxytocin and human chorionic gonadotrophin (hCG) on ovulation and conception. A total of 100 women with anovulatory infertility were allocated into two equal groups to take clomiphene citrate plus hCG or clomiphene citrate plus oxytocin. The size and number of follicles by transvaginal sonography determined the administration of hCG or oxytocin. The serum progesterone concentration was measured to provide evidence for ovulation. The ovulation and pregnancy rate of the two groups were compared. There was no significant difference between the groups with respect to mean number of follicles, mean follicular size and rate of ovulation in three cycles. The rate of pregnancy was higher in the oxytocin group compared with the hCG group (12% vs 4%) but it failed to reach statistical difference (p = 0.140). Mild pain was the only side-effect observed in the two groups. Oxytocin was found to be a viable alternative to hCG for triggering ovulation in infertile patients.